2019
DOI: 10.1002/jbt.22302
|View full text |Cite
|
Sign up to set email alerts
|

Gastrodin attenuates neuroinflammation in DOI‐induce Tourette syndrome in rats

Abstract: Objective: Tourette syndrome (TS) is a chronic neuropsychiatric disorder. Its clinical manifestations are involuntary and recurrent muscle twitch, resulting in motor twitch and occurrence twitch. Traditional Chinese medicine has obvious advantages in treating TS. The aim of this study was to investigate the effects and mechanism of gastrodin on 1-(2,5-dimethoxy-4-iodophenyl)-2-aminopropane (DOI)-induced TS in rats. Methods: TS model was induced by DOI. Behaviors in TS rats were detected. The striatum, serum in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
17
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(20 citation statements)
references
References 18 publications
3
17
0
Order By: Relevance
“…It has been reported that Gas has beneficial effects on many CNS diseases including TS. [23][24][25] Here, we found that Gas could ameliorate tic-like symptoms, including stereotypy score, nodding numbers, number of times to enter the central area and the total movement distance of the rats with TS induced by IDPN, which were consistent with previous research. 24,25 In the present study, we further elaborated the anti-tics effects of Gas on the rats with TS induced by IDPN and the potential mechanism.…”
Section: Discussionsupporting
confidence: 91%
See 4 more Smart Citations
“…It has been reported that Gas has beneficial effects on many CNS diseases including TS. [23][24][25] Here, we found that Gas could ameliorate tic-like symptoms, including stereotypy score, nodding numbers, number of times to enter the central area and the total movement distance of the rats with TS induced by IDPN, which were consistent with previous research. 24,25 In the present study, we further elaborated the anti-tics effects of Gas on the rats with TS induced by IDPN and the potential mechanism.…”
Section: Discussionsupporting
confidence: 91%
“…Our findings are consistent with the results of previous studies showing that Gas and Tia have similar therapeutic effects on the behaviors of rats with TS. 24,25 Currently, an increasing number of studies have demonstrated that malfunction of CSTS circuits, which are involved in cognitive, sensorimotor, and emotional functions, may be related to the development of a variety of neuropsychiatric diseases, including TS. 34,35 Abnormal amino acid neurotransmitters, such as Glu and GABA, involved in the CSTS circuits, are closely associated with the occurrence of TS.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations